(untitled) (International Journal of Banking and Finance, 2023)
The purpose of this study was to synthesize the findings of previous studies on the relationship between religiosity and saving behaviour by using a meta-analysis approach. It also sought to determine the strength of the relationship, besides its direction. Eleven studies which met the five criteria and four techniques used in the study were used as samples for the meta-analytic analysis. The size of the effect in each study was then determined by Pearson’s product-moment correlations (r). To estimate the average distribution of relationship true effects, the Fisher r-to-z transformation and random-effects methods were used. The empirical evidence showed that there was a positive correlation between religiosity and saving behaviour. However, according to Guilford’s convention, the true effect size (r = 0.303) would mean that religiosity had a weak correlation with saving behaviour. It is recommended that authorities and financial institutions use the findings of this study to develop plans focused on advocating and facilitating saving behaviour among religious people.